NEXUS BETWEEN THRIFTING AND GDP GROWTH IN INDONESIA’S TEXTILE AND WEARING APPAREL MANUFACTURING: ARDL AND SENTIMENT ANALYSIS APPROACH - Rahmanto, Karina Cindy; Hasanah, Lailatul; Ramadhan, Arfian Kurniawan; Kartiasih, Fitri (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2025)
Introduction: The rise of used clothing imports has sparked concerns about its economic impact, particularly on Indonesia’s textile and apparel industry. Methods: This study employs a mixed-methods approach, combining quantitative (ARDL model) and qualitative (sentiment analysis) methods. It analyzes GDP, Google Trend Index (GTI), and used clothing import data from 2018–2023 to assess the economic impact of thrifting. Results: This study analyzes the impact of thrifting on the GDP of Indonesia's textile and apparel industry subsector. The findings indicate that thrifting has a significant negative effect on the sector's GDP, while sentiment analysis reveals that 81.90 percent of public sentiment on Twitter expresses positive views toward thrifting. Conclusion and suggestion: This study concludes that thrifting harms the GDP of Indonesia's textile and apparel industry subsector. This finding is reinforced by the high public interest in thrifting, as reflected in the predominantly positive sentiment on Twitter. In response, policymakers and industry stakeholders should strengthen the enforcement of existing regulations and focus on enhancing the competitiveness of local products.